Relationship Between Reward System and Turnover Intention: The Mediating Role of Organizational Commitment - Bartaula, Aashish (KIC International Journal of Social Science and Management, 2023)
The purpose of this study is to investigate the link between reward systems, organizational commitment, and employee turnover intention in Nepal’s commercial banking industry. The research employs a quantitative technique as well as a descriptive, correlational research design. Three hundred and eighty structured forms were distributed to full-time workers of six commercial banks, three government-owned institutions, and three private banks. To analyze the data and test the research hypotheses, confirmatory factor analysis and structural equation modeling were utilized. The study’s findings show a negative relationship between reward systems and organizational commitment and employee turnover intention. According to the findings, the correct compensation scheme can increase employee engagement while decreasing the desire to quit. In addition, the study discovers that organizational commitment completely mediates the association between reward schemes and employee turnover intention. This study contributes to the body of knowledge on employee turnover intentions in Nepal’s banking industry. The findings underscore the necessity of developing and implementing effective reward systems that can increase employee engagement while decreasing the likelihood of turnover. Organizations may take proactive actions to retain employees and enhance their performance by knowing the variables that drive employee turnover intention.